Money manager capitalism and the global financial crisis - L. Randall Wray (Levy Economics Institute of Bard College, 2009)
This paper applies Hyman Minsky's approach to provide an analysis of the causes of the global financial crisis. Rather than finding the origins in recent developments, this paper links the crisis to the long-term transformation of the economy from a robust financial structure in the 1950s to the fragile one that existed at the beginning of this crisis in 2007. As Minsky said, 'Stability is destabilizing': the relative stability of the economy in the early postwar period encouraged this transformation of the economy. Today's crisis is rooted in what he called 'money manager capitalism,' the current stage of capitalism dominated by highly leveraged funds seeking maximum returns in an environment that systematically under-prices risk. With little regulation or supervision of financial institutions, money managers have concocted increasingly esoteric instruments that quickly spread around the world. Those playing along are rewarded with high returns because highly leveraged funding drives up prices for the underlying assets. Since each subsequent bust wipes out only a portion of the managed money, a new boom inevitably rises. Perhaps this will prove to be the end of this stage of capitalism-the money manager phase. Of course, it is too early even to speculate on the form capitalism will take. I will only briefly outline some policy implications.
Keywords: E02; E12; E32; E44; G01; G2; 330; Hyman Minsky; money manager capitalism; financial crisis; financial instability hypothesis; asset-backed securities; commodities ftures markets